PENGARUH DEWAN KOMISARIS, DEWAN PENGAWAS SYARIAH, FINANCING TO DEPOSIT RATIO (FDR), DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS. - Raka Dwi Pangestu; Suryo Budi Santoso (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
This study aims to determine the effect of the board of commissioners, sharia supervisory board, financing to deposit ratio, and company size on profitability as proxied by ROA (Return On Assets) in Islamic commercial bank companies registered with the Financial Services Authority for the period 2014-2018. The sampling technique used is the purposive sampling technique to obtain a sample of 14 companies with 70 observations. The data analysis technique used is multiple linear regression analysis with the help of the SPSS program. This study indicates that the variables of the board of commissioners, sharia supervisory board, and financing to deposit ratio do not affect profitability. However, another variable, namely the size of the company, has a positive effect on profitability.